The Trade Effects of the EU-South Korea Free Trade Agreement: Heterogeneity Across Time, Country Pairs, and Directions of Trade within Country Pairs - Benjamin Jung (Open Economies Review, 2022)
The EU-South Korea Free Trade Agreement, which entered into force in 2015, is an example of so-called "second-generation" regional trade agreements. Using the gravity equation and drawing on a novel dataset on trade in manufacturing goods (Monteiro in World Trade Organization, Geneva,~ 42 ), I explore the heterogeneity in the trade effects of this agreement across time (anticipation and phasing-in/delayed adjustment), country pairs, and across trading directions within pairs (exports versus imports). First, the positive trade effect after the announcement vanished one year prior to entry into force. Second, on average exports of EU countries to South Korea rise, while imports of EU countries are not significantly affected, potentially reflecting differences in ex ante trade policies. Third, additional imports caused by the agreement are larger for those EU countries where South Korea accounted for a large share of extra-EU imports already before the agreement.
Keywords: F13; F14; F15; 330; International Trade; Structural Gravity; EU-South Korea Free Trade Agreement